Role of protected areas in faunal conservation (Zoological Records and Reviews, 2024)
Protected areas (PAs) remain the cornerstone of global faunal conservation strategy, yet their effectiveness variessubstantially with management quality, size, connectivity, and surrounding landscape context. This study evaluates theconservation effectiveness of 48 protected areas spanning five IUCN management categories (I-VI) across Sweden,France, and the Netherlands using standardised multi-taxon biodiversity surveys (birds, mammals, herpetofauna, andground beetles; n = 24,817 individual records across 384 taxa), PA governance quality scores, and paired outside-PAreference site comparisons. Species richness inside PAs exceeded paired outside-PA reference sites by a mean of 38.4+- 6.8% across all four taxonomic groups (paired t-test t(47) = 8.92, p < 0.001). PA effectiveness -- measured as theinside-outside biodiversity ratio -- was significantly predicted by management effectiveness score (METT; beta = 0.48 +-0.08, p < 0.001), PA area (beta = 0.31 +- 0.07, p < 0.001), and connectivity index (beta = 0.24 +- 0.07, p = 0.001). IUCNCategory I/II strict reserves showed the highest mean inside-outside biodiversity ratio (1.74 +- 0.18), while Category V/VIprotected landscapes showed the lowest (1.18 +- 0.12), but Category V/VI sites supported significantly higher functionaldiversity of farmland-adapted taxa than strict reserves. Thirty-one percent of PAs scored below the METT thresholdassociated with measurable biodiversity benefit (score < 50/100), constituting 'paper parks' with biodiversity levelsindistinguishable from outside. Connectivity to other PAs was the strongest predictor of mammal occupancy within PAs(beta = 0.54 +- 0.09), underscoring the importance of ecological networks over isolated reserve expansion. These resultssupport evidence-based target-setting under the Kunming-Montreal Global Biodiversity Framework 30x30 goal.